Pengaruh Displin Kerja, Keselamatan dan Kesehatan Kerja terhadap Produktivitas Karyawan PT Santoso Teknindo di Tangerang - Sulaeman, Asep; Rahayu, Yustina Dwi; Hadi, Reza Khairul; Komarudin, Komarudin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research aims to examine the impact of work discipline, occupational safety, and health on employee productivity at PT Santoso Teknindo. The research method employed is a quantitative approach, using several tests including data instrument testing, classical assumption testing, correlation coefficient analysis, coefficient of determination analysis, simple linear regression, multiple linear regression, t-test (partial test), and f-test (simultaneous test). The objective is to determine whether there is a relationship between work discipline, safety, health, and employee productivity at PT Santoso Teknindo. The results indicate that work discipline positively affects productivity, with a significant statistical value. Similarly, occupational safety also positively influences employee productivity. This suggests that both work discipline and occupational safety have a significant and positive effect on employee productivity when analyzed individually. Furthermore, when examined together, both work discipline and safety & health significantly influence productivity, confirming a strong simultaneous effect. The implications of these findings suggest that improving work discipline and enhancing occupational safety and health can significantly boost employee productivity. Organizations, particularly PT Santoso Teknindo, may consider prioritizing these areas to foster a productive work environment. Implementing policies that support these factors could lead to higher efficiency and performance, ultimately contributing to the overall success of the company.